Oral Candidiasis in patients with diabetes mellitus - Gladys Aída Estrada Pereira; Maricel Marquez Filiu; José Manuel Díaz Fernández; Liliet Antonia Agüero Despaigne (Centro Provincial de Información de Ciencias Médicas, 2015)
A descriptive and cross-sectional study of 75 patients with diabetes mellitus who presented oral candidiasis, treated in the stomatological service of the Specialties Polyclinic of "Saturnino Lora Torres" Teaching Provincial Clinical Surgical Hospital in Santiago de Cuba was carried out, from March, 2013 to the same month in 2015, in order to evaluate the results of the clinical and histopathologic diagnosis of the mentioned affection.  The samples for biopsies were fixed and processed with the classic technique of inclusion in paraffin; they were colored with a special stain of Schiff periodic acid, which confirmed the existence of cellular changes.  There was a prevalence of male sex, the 60 years and over age group; the absence of clinical symptoms, the hard palate and the corner of the mouth as the sites of greater prevalence and the erythematous candidiasis as the most common clinical form.  The presence of pathogen hyphae and yeast-like cells were the most outstanding histopathologic findings.